Defesa dos direitos humanos na Paraíba durante a ditadura militar: da campanha da anistia ao movimento de revisão da Lei nº 6.683/1979 - Silva, Janaína Gomes da (2023)
The research aims to analyze the theme of the Brazilian Amnesty Law of 1979, from the first movements around the political institute to the present day. Furthermore, it seeks to demonstrate the role of Paraíba in the Amnesty Campaign through the actions of civil society movements. The study is justified by the need for empirical research in order to verify the peculiarities of the civil-military dictatorship in the state of Paraíba. The Amnesty Law remains an object of discussion in both the legal and academic spheres because it allowed the impunity of agents of repression involved in crimes against humanity, namely: torture, homicide, and forced disappearance of political opponents during the military regime. The validity of the law in the Brazilian State impedes the advancement of transitional justice policies. This research seeks to elucidate the mobilizations of civil sectors of Paraíba society in the Amnesty Campaign during the 1970s, which contributed to the struggle for the defense of human rights, as well as to support the idea of the need to revise Law 6.683/1979, as it is unconventional and in conflict with the provisions of International Human Rights Law. The work was carried out through a bibliographic review; reading and analysis of official documents produced by the State, such as those made available at the Fundo do Serviço Nacional de Informações do Arquivo Nacional; field research at the João Pessoa archives in order to make a historical reconstruction of what the local press reported about the amnesty between 1974 and 1979; analysis of decisions handed down by the Inter-American Court of Human Rights; examination of the judgment of ADPF 153 and other cases related to amnesty. Finally, it is worth mentioning that this PhD Thesis is placed in the field of the New Political History in dialogue with Human Rights theorists, such as Norberto Bobbio, Flávia Piovesan, Valerio Mazzuoli, Glenda Mezarobba, among others.